PROXIMATE AND MINERAL COMPOSITION OF FRESHWATER FISHES - Natarajan, M V; Sreenivasan, A (Indian Journal of Fisheries, 2011)
DATA on chemical composition of many of the freshwater fishes of ourcountry is not available and hence an attempt has been made to analyse asmany as thirty-six species. The chemical composition of fish varies widelyfrom species to species and season to season. There is also individual variationin the same species. A knowledge of chemical composition is essentialin order to compare its value as food with other protein foods. Stansby(1954) has elaborated on the importance of chemical analysis.